2017
DOI: 10.1007/s40415-017-0371-6
|View full text |Cite
|
Sign up to set email alerts
|

“Cerrado” restoration by direct seeding: field establishment and initial growth of 75 trees, shrubs and grass species

Abstract: The coexistence of grasses, herbs, shrubs and trees characterizes savannas; therefore, to restore such ecosystems one should consider reintroducing all these growth forms. Currently, little is known about field establishment of most ''Cerrado'' (Brazilian savanna) species that could be used for restoration purposes. Most knowledge on restoration is focused on planting seedlings of tree species from forest physiognomies. Alternatively, direct seeding can be an appropriate method to reintroduce plants of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
2
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 34 publications
4
80
2
20
Order By: Relevance
“…Therefore, additional techniques are necessary to reintroduce woody plants (shrubs and subshrubs) (Pilon et al ), which are more abundant in dry than in wet grasslands. Complementary techniques such as direct seeding of shrubs and subshrubs (Silva et al ; Pellizzaro et al ) or deeper extraction of underground structures and soil from areas that will be suppressed (Ferreira et al ) can be combined with grasses and forbs transplantation and topsoil translocation to restore all growth forms that characterize old‐growth cerrado grasslands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, additional techniques are necessary to reintroduce woody plants (shrubs and subshrubs) (Pilon et al ), which are more abundant in dry than in wet grasslands. Complementary techniques such as direct seeding of shrubs and subshrubs (Silva et al ; Pellizzaro et al ) or deeper extraction of underground structures and soil from areas that will be suppressed (Ferreira et al ) can be combined with grasses and forbs transplantation and topsoil translocation to restore all growth forms that characterize old‐growth cerrado grasslands.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have provided support for temperate‐grassland restoration on a large scale (Kiehl ). The effectiveness of such techniques in tropical grasslands and savannas has been recently assessed, with promising results in some cases (Le Stradic et al , ; Ferreira et al ; Pellizzaro et al ; Pilon et al ; Gomes et al ). Nonetheless, all these techniques depend on the existence of well‐conserved remnants of natural vegetation that can be donor ecosystems of seeds, plants, and topsoil for restoration.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the restoration of the Cerrado (Brazilian savanna) herbaceous layer have identified promising techniques, such as direct seeding, topsoil and hay transfer, and the transplantation of mature herbaceous plants (Le Stradic et al 2014, 2016Ferreira et al 2015;Pellizzaro et al 2017;Gomes et al 2018;Pilon et al 2018aPilon et al , 2018bSampaio et al 2019). Although some of these practices showed good results, such as direct seeding (Pellizzaro et al 2017;Sampaio et al 2019), it is important to develop alternatives, offering new perspectives to overcome difficulties in the restoration techniques studied and applied so far (Buisson et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, seeding and topsoil methods are pointed out as the best cost-effective methods, with much lower costs than planting nursery-raised seedlings, but they also lead to some problems, like species dominance (Pellizzaro et al, 2017;Sampaio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…First, choice of restoration method in the Cerrado depends on the history of land use in the area. Natural regeneration, assisted or not, is successful only where the subterranean structures of the Cerrado plant species were not destroyed, what happens in most agriculture models (Pellizzaro et al, 2017). Currently, seeding and topsoil methods are pointed out as the best cost-effective methods, with much lower costs than planting nursery-raised seedlings, but they also lead to some problems, like species dominance (Pellizzaro et al, 2017;Sampaio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%